Aerobic Exercise and Its Effect on Oxytocin Level and Labor Progression. (March 2017) - Irianti, S; Ginandjar, A B; Krisnadi, S R; Effendi, J S; Nataprawira, D; Gandamihardja, S
Abstract: Nowadays, Obstetrical management has turned into active management. Aerobic exercise has already been performed by pregnant women and recommended by the American College of Obstetrics and Gynecology. It is known to have many benefits for labor progress and could decreased cesarean section and assisted vaginal delivery rate. This might be caused by the increase of endogenous oxytocin level. This is an experimental study involving 40 patients in Hasan Sadikin General Hospital, Awi Bitung Islamic Hospital and Kota Bandung District Hospital that met the inclusion criteria and divided into 2 groups: a group that performed aerobic exercise regularly and the other who did not. The characteristic of the subject (age, gestational age and body birth weight) showed no significant differences between two groups. Between two groups, there were significant association on mode of delivery and length of active phase of labor and the percentage of plasma oxytocin level. There was no significant association between the two groups in duration of the first stage, second stage and oxytocin level with the length of aerobic exercises. This study concluded that regular aerobic exercise in pregnant woman increases oxytocin level and improve labor progress.